Wrench-Slip Reversals and Structural Inversions: Cenozoic Slide-Rule Tectonics in Sundaland - H.D. Tjia (Indonesian Journal on Geoscience, 2014)
DOI: 10.17014/ijog.v1i1.174Most of continental Southeast Asia, that is, Sundaland and Indosinia, achieved a relative tectonic stability by the beginning of the Cenozoic. Since then a strong tectonic activity in Sundaland has been restricted to existing regional fault zones and to regional slow, vertical crustal movements elsewhere that produced small to very large sedimentary basins. On the other hand, regional deformation of Indosinia as a consequence of ductile shearing has continued into the Paleogene. Since the Oligocene, the northern part of Sundaland and Indosinia have been extruded differentially towards southeast along the Red River, Wang Chao (or Mae Ping, or Tonle Sap), and Three Pagodas - Axial Malay fault zones. The initial cause has been attributed to hard collision between Subplate India with Megaplate Eurasia. Plate dynamics in the region have changed substantially since Mid-Miocene as to force wrench-slip reversals along the major fault zones in Sundaland as well as in Indosinia. Concomitant structural inversions are demonstrated on seismic sections. In the core of Sundaland, earlier transtensional wrenching was succeeded by transpressive strike-slip faulting that on major faults of the Malay Basin manifested in reversals of sense. From the Hinge-line fault eastward, the transtensional left wrench slip was succeeded by transpressional dextral slip, while in the region to its west the wrench-slip kinematics was an earlier transtensional right slip followed by transpressional left slip. In the Strait of Malacca and eastern margin of Sumatra, right-lateral wrenching in the Neogene has been common. In certain places it could be established a wrench-slip of transtensional character in Oligocene-Early Miocene, and the transpressional wrench movement occurred mainly during the Middle to Late Miocene. The remarkable coincidence of termination of spreading of the South China Basin in Langhian, and that of the West Philippine and Caroline basins during Mid-Miocene invites further study.